Evaluation of STE(A)M Education: An Analysis of Research and Practices from 2014 to 2023 - Wong, Billy T.M.; Cheong Li, Kam; Liu, Mengjin (Journal of educational technology development and exchange, 2025)
STEM (Science, Technology, Engineering, and Mathematics) and STEAM (by including Arts) education (hereafter STE(A)M education) has been widely studied and practiced. Evaluation plays an important role in assessing and improving the effectiveness of relevant initiatives. Although there has been extensive research on evaluating STE(A)M education, little attention has been paid to examining the patterns of said evaluations. To address the research gap, this paper analyses relevant work on the evaluation of STE(A)M education practices with respect to their countries/regions, levels of education, discipline domains, pedagogical approaches, objectives of evaluation, evaluation areas, as well as data collection and analysis methods. It covers 339 publications from 2014 to 2023 which were collected from Scopus. Based on content analysis, the findings reveal a global interest in STE(A)M education and its evaluation, with a focus on secondary education and the core STEM subjects. The findings also highlight a diverse range of pedagogical approaches being used in STE(A)M education, with problem-based learning being the most popular. There has been a shift in evaluation objectives over the years, indicating a greater emphasis on determining the effectiveness of STE(A)M education and improving student learning performance. While academic achievement remained the most commonly evaluated area, there has been growing recognition of the importance of evaluating skills and competencies in STE(A)M education. The results also show a wide range of data sources and data analysis methods adopted for the evaluations.